2017
DOI: 10.14527/pegegog.2017.014
|View full text |Cite
|
Sign up to set email alerts
|

Children, parents and tablets: Preschool children's tablet use

Abstract: The aim of this study is to examine preschoolers' tablet use and evaluate parents' opinions concerning it. To this end, the study made use of a case study design which is a means of qualitative research. The sample of the study consists of five preschoolers and their parents. The study data was gathered with observations related to preschoolers' tablet use, examinations of the applications in children's tablets and semi-structured interviews with parents. The analysis framework for tablet use was structured ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This finding is also supported by the evidence in the literature. Previous studies have shown that (Guedes et al, 2019;Kaya, 2020;Radesky et al, 2015;Sivrikova et al, 2020;Yılmaz Genç & Fidan, 2017) establishing parental control and limiting time act as a protective factor against negative effects of ICT usage. Parents' monitoring of children's ICT use and establishing time limits can be considered as positive practices to protect children from the negative effects of ICT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is also supported by the evidence in the literature. Previous studies have shown that (Guedes et al, 2019;Kaya, 2020;Radesky et al, 2015;Sivrikova et al, 2020;Yılmaz Genç & Fidan, 2017) establishing parental control and limiting time act as a protective factor against negative effects of ICT usage. Parents' monitoring of children's ICT use and establishing time limits can be considered as positive practices to protect children from the negative effects of ICT.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted in Turkey investigated the views of parents on the use of ICT by preschool children. These studies examined the relationship between university graduate parents' perceptions (Kaya, 2020) and television (Güngör, 2014), technology use (Biber et al, 2019), smartphones (Genç, 2014), new media (Durmuş & Övür, 2021), tablets (Yılmaz Genç & Fidan, 2017), the relationship between technology use and social skills and social status (Gülay Ogelman et al, 2018), the relationship between digital media use and self-regulation skills, and technology addiction (Canaslan Akyar & Sungur, 2022) and compulsive behaviors (Dere, 2022). Several international studies have investigated the relationship between computers (Hatzigianni & Margetts, 2014), tablets and smartphones (Ateş & Durmuşoğlu Saltalı, 2019;Guedes et al, 2019), screens (Assathiany et al, 2018;Waisman et al, 2018), digital technology (Gjelaj et al, 2020;Jabbar et al, 2019), problematic smartphone use (Park & Park, 2021), digital device usage for learning (Sivrikova et al, 2020), parents' technology usage, the relationship between parental attitudes and children's age (Lauricella et al, 2015), mobile device usage frequency, preferred application types, parents' beliefs and strategies (Papadakis et al, 2022), children's mobile device use in low-income rural areas (McCloskey et al, 2018), and concept of ICT (Vodopivec & Samec, 2017).…”
Section: Introductionmentioning
confidence: 99%